Sistem Ekonomi Spiritualitas : Sebuah Seminar Online - Gregorius Daru Wijoyoko; Andarweni Astuti; Dicky Apriyanto (Jurnal Pengabdian Kepada Masyarakat, 2023)
The purpose of this online social service is to present the importance of solidarity in economic principles for better prospective prosperity. This online social service has educational material based on the social teachings of the Church, Article Gaudium Evangelii and previous research from prof. Lazlo Zsolnai who stated that an economic system with spirituality has a solutive effect on the economic crisis. This Community Service emphasizes spirituality embodied in solidarity needs to be implemented. The background to this Community Service Event is that this was due to the emergence of a massive economic crisis during the pandemic since early 2020. Therefore, the need for scholars to try to overcome the structural causes of poverty. The results shows that 63% participants believe that Spirituality, or love for God and others will trigger a love for life and an economic system that is in solidarity for the common good.